The Influence of Knowledge Quality, Self-Efficacy, and Reciprocity on Online Entrepreneurial Knowledge-Sharing Activities of Muslim Entrepreneurs on Facebook - Fakhrudin Fakhrudin; Tata Sukayat; Shaifurrahman Shaifurrahman (Communicatus: Jurnal Ilmu komunikasi, 2024)
The study examines the influence of knowledge quality, self-efficacy, and reciprocity among Muslim entrepreneurs on Facebook. It employed a quantitative approach with an observation method. The findings reveal that knowledge quality positively affects online entrepreneurial knowledge-sharing activities. High-quality knowledge promotes effective collaboration and sharing within the entrepreneur community. However, self-efficacy and reciprocity were not found to influence these activities significantly. Therefore, in this context, self-confidence in one's abilities and expectations for reciprocity may be less important than previously thought. This study suggested that knowledge sharing should focus more on improving the quality of knowledge shared than fostering self-efficacy or reciprocity as higher quality knowledge could contribute to the growth and success of Muslim entrepreneurs by encouraging more effective knowledge-sharing strategies.